Treatment of Prepubertal Labial Adhesion: A Case Report - Ibnuzaer Khalilullah; Bobby Indra Utama; Yulia Margaretta Sari (Fakultas Kedokteran Universitas Andalas, 2026)
Introduction : Labial adhesion is a condition in which the labia minora adhere to each other, either partially or completely, and is most commonly observed in prepubertal girls. The highest incidence typically occurs between the ages of 3 months and 6 years, a period during which lower estrogen levels make the vulvar mucosa more susceptible to irritation and adhesion. Objective : To report and discuss a rare case of labial adhesion on prepubertal. Methods : A prepubertal girl diagnose with labial adhesion at Dr. M. Djamil Central Hospital was reported and discuss the management. Result : A four-year-old girl was referred to the outpatient urogynecology clinic by a network hospital for labial adhesion. Upon general assessment, the child's development appeared appropriate for her age. Her medical history did not reveal any significant illnesses, surgical procedures, or history of sexual abuse, and her general physical examination was normal. Upon inspection, the labia majora were normal, but he labia minora appeared fused with a 0.2 cm gap at the proximal area of the adhesion. The adhesions appear thick and non-transparent For this patient, we decided to proceed with excision of the labial area without first attempting estrogen therapy. Seven days post-operation, the patient returned for a follow-up visit in good condition. The surgical wound was dry, urination was normal, and the examination showed a normal vaginal opening. Conclusion: From this case report, we conclude that for long-standing labial adhesion characterized by tissue thickening, labial excision is the appropriate and effective treatment option.